Molecular Profiling in Non-Small-Cell Lung Cancer: A Single-Center Study on Prevalence and Prognosis - Mustafa Özgür Arıcı; Bora Demirkan; Ebru Taştekin; Derya Kıvrak Salim (Current Oncology)
The aim of this study is to evaluate the prognostic value of molecular profiling in patients with metastatic non-small-cell lung cancer (NSCLC). This single-center study included patients diagnosed and treated between July 2020 and April 2024. The molecular profiles of patients detected by either next-generation sequencing or conventional methods were reviewed retrospectively. Survival analyses were conducted based on the targetable alterations and treatments received. Seventy patients were included, with a median age of 65 years and a median overall survival (OS) of 13 months. Of all patients, 56 (80%) had at least one molecular alteration, and the most frequent alteration was TP53 (52.9%), followed by KRAS (20%) and EGFR (8.6%). Eighteen patients (25.7%) had an alteration amenable to targeted therapy. Patients who could reach a matched targeted therapy at any treatment line exhibited a longer median OS compared to those who could not (not reached vs. 6.9 months, p = 0.042). Patients with a targetable alteration for first-line treatment demonstrated a longer progression-free survival compared to those without a targetable alteration (not reached vs. 4.9 months, p = 0.006). According to current guidelines, conducting molecular testing to identify all potential targetable alterations in NSCLC is the cornerstone of the treatment decision process. The survival analysis in this study emphasized the impact of the use of targeted therapies on the survival outcomes.